The New AI Act and its impact on the competitiveness of businesses operating in the European Union - Briedis, Nauris (Riga Graduate School of Law, 2024)
In a world where technology advances at such a fast pace and is at the forefront in many fields of everyday life, the newest addition is the appearance of Artificial Intelligence (AI). While it may seem exciting and beneficial to us at first glance, it is easy to lose sight of potential risks that it may invoke on all of us. The European Union has attempted to ensure safety of humans and promote the development of ethical and safe artificial intelligence systems by passing the new Artificial Intelligence Act in the beginning of 2024. This Regulation aims to implement different risk categories for AI systems, as well as create a necessity for conformity assessments, integrate transparency requirements and different safeguards to ensure the protection of personal data – all with the goal of increasing the level of trust that humans have towards artificial intelligence systems. Although this Regulation has been highly anticipated, many argue that this Act will over regulate artificial intelligence and stifle innovation by creating additional administrative burdens for businesses and harm competition in the single market. Therefore, a thorough analysis of the AI Act and its relationship between competition law of the European Union is crucial to understand whether or not such allegations have factual grou
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Competition law; Artificial Intelligence Act; General Data Protection Regulation; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law